Identifier les étudiants vulnérables en première année à l’université - Sylviane Bachy; Dorothée Baillet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In French-speaking Belgium, most university courses are in open access. Combined with the existence of wide disparities between types of secondary education, secondary schools and even options within an institution, these two factors contribute to make university entry a particularly critical period for many students. In this context, it is essential to identify students who need specific pedagogical support to give them best chance of success. That was the objective of a work carried out at the Université libre de Bruxelles. The learning support service has developed a profiling questionnaire with five headings (metadata, perception of the student profession, indicators, volitional strategies, digital skills). It is offered to first-time applicants. In 2022-23, it collected responses from 3955 students in the 12 faculties of the university, including 3742 in the first-year students. First analyses show interesting variations in the proportion of profiles (conventional and at risk) from one faculty to another. Combinations of characteristics are intended to better identify success nedir.université, accompagnements aux apprentissages, profils, questionnaire